1964
DOI: 10.1172/jci104996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine in Man: Augmentation of Sodium Excretion, Glomerular Filtration Rate, and Renal Plasma Flow*

Abstract: Dopamine (3,4-dihydroxyphenylethylamine) is considered to be the immediate metabolic precursor of norepinephrine (1), from which it differs by the absence of a P-OH group. Despite this chemical similarity, previous studies of the action of dopamine (2-9) have demonstrated that many of the circulatory and metabolic effects of this catecholamine are different from those produced by norepinephrine. Horwitz, Fox, and Goldberg (6) observed that intravenous administration of dopamine to normal subjects produced cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
148
0
14

Year Published

1975
1975
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(168 citation statements)
references
References 26 publications
6
148
0
14
Order By: Relevance
“…The renal effects of fenoldopam demonstrated in this study are similar to those first reported with low-dose dopamine by McDonald et al 29 That these renal effects are due to activation of the dopamine-1 receptor by dopamine was later shown during concomitant therapy with phenoxybenzamine30; such additional therapy is not necessary with the specific dopamine-1 agonist fenoldopam. In addition to recent studies demonstrating improved renal function with intravenous fenoldopam in normal subjects,31 or patients with heart failure,21 there are now several studies in patients with various degrees of hypertension that also have improved renal function during dopamine-1 receptor activation.…”
Section: Discussionsupporting
confidence: 89%
“…The renal effects of fenoldopam demonstrated in this study are similar to those first reported with low-dose dopamine by McDonald et al 29 That these renal effects are due to activation of the dopamine-1 receptor by dopamine was later shown during concomitant therapy with phenoxybenzamine30; such additional therapy is not necessary with the specific dopamine-1 agonist fenoldopam. In addition to recent studies demonstrating improved renal function with intravenous fenoldopam in normal subjects,31 or patients with heart failure,21 there are now several studies in patients with various degrees of hypertension that also have improved renal function during dopamine-1 receptor activation.…”
Section: Discussionsupporting
confidence: 89%
“…Frusemide is with these acute changes there is an increased thus a useful tool with which to study the kidney excretion of both PGE2 and the stable break-as it provides a convenient method of acutely stimulating a number of different systems. PGE2, PGI2 (Fulgraff et al, 1974) and dopamine (McDonald et al, 1964;Hollenberg et al, 1973;Smit et al, 1988) are renal vasodilators. All stimulates renal PGE2 synthesis (Aitken & Vane, 1973;Frolich et al, 1975) and a high salt diet suppresses PGE2 production.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism involves an increase in inotropy by direct stimulation of cardiac P,-adrenoceptors and through the release ofnoradrenaline (Farmer, 1966;Goldberg, 1972). Additional advantages stem from the increase in renal blood flow and natriuresis caused by dopamine receptor stimulation (McDonald et al, 1964;Meyer et al, 1967). However, the usefulness of dopamine in the treatment of acute heart failure is ' Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%